Involving Youth in the Community Development Process - Rosemary Barnett; Mark Brennan (EDIS)
“As communities face challenges and opportunities to help serve their residents, they’re often faced with a lack of resources, including volunteers. However, many parents are discovering that their children may not only want to volunteer, but many teenagers are required to volunteer if they’re pursuing a future in college.” This 2-page Family Album Radio transcript was written by Rosemary Barnett and Mark Brennan, and published by the UF Department of Family, Youth and Community Sciences, March 2012.